2008
DOI: 10.3399/bjgp08x279670
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex interaction in reported help seeking in response to chest pain

Abstract: There is a growing literature suggesting that access to cardiology services is affected by age. However, there is a dearth of studies that have considered age and sex in conjunction. AimThis study aims to examine the impact of age, and its interaction with sex, on reported healthcare seeking, based on responses to symptom vignettes, in an attempt to standardise symptomatology across all responders. Design of studyA cross-sectional survey design was utilised. SettingPrimary care. MethodA random sample of 911 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…However, Adamson et al observed that the tendency to look for health care because of thoracic pain, especially among women, increased with age 40 , which can be interpreted as a similar attitude to that approached in our investigation.…”
Section: Discussionsupporting
confidence: 85%
“…However, Adamson et al observed that the tendency to look for health care because of thoracic pain, especially among women, increased with age 40 , which can be interpreted as a similar attitude to that approached in our investigation.…”
Section: Discussionsupporting
confidence: 85%
“…This can be explained by a rising prevalence of chronic problems (e.g., musculoskeletal or cardiovascular ones) and by the increased rate of healthcare seeking in patients aged 60 years and over and by the ascending frequency of cardiovascular check-ups in these patients. [ 16 17 ] Other studies reported chest pain frequencies of about 1.5% (Sweden), 0.7% (Iceland), and 15.5/1000 patient-years (Great Britain) but similar findings especially the nearly doubling of the chest pain frequency from younger adults to the elderly, as seen in the Dutch Transition Project but also a first peak in the age group of 21–40 years. [ 6 7 18 ] The variation in the reported consultation frequencies [ Table 4 ] may be explained by the different geographic backgrounds and different sampling methods of the mentioned studies.…”
Section: Discussionmentioning
confidence: 80%
“…With respect to age, youth also appears to be a factor lowering rates of presentation and uptake of health checks (Adamson et al . , Dalton et al . , Cook et al .…”
Section: Resultsmentioning
confidence: 99%
“…Some studies (Donyai & Van den Berg 2009, Labeit et al 2013) agree that people from less advantaged communities are more likely to access CHD risk screening programmes, while others disagree (Horgan et al 2010, Gidlow et al 2015, Chang et al 2015, Cook et al 2016. With respect to age, youth also appears to be a factor lowering rates of presentation and uptake of health checks (Adamson et al 2008, Dalton et al 2011, Cook et al 2016, Robson et al 2016. Given the significant prevalence of overweight, obesity and associated cardiovascular risk among 45-to 64-year olds in England, the reviewed evidence suggests that preventive action could be more positively targeted at this age group.…”
Section: Variations Across the Care Pathwaymentioning
confidence: 99%